Diabetes Mellitus and Cardiovascular Prevention: The Role and the Limitations of Currently Available Antiplatelet Drugs - A. Tufano; E. Cimino; M. N. D. Di Minno; P. Ieranò; E. Marrone; A. Strazzullo; G. Di Minno; A. M. Cerbone (International Journal of Vascular Medicine)
Diabetes mellitus (DM) is associated with macrovascular and microvascular complications. Platelets have a “key role” in atherogenesis and its thrombotic complications in subjects with DM. Moreover, the concomitant presence of multiple “classical” cardiovascular risk factors in diabetic subjects contributes to enhanced atherothrombotic risk. Antiplatelet agents are effective in primary and secondary prevention of arterial thrombosis (cardiovascular events, ischaemic stroke, and peripheral arterial occlusive disease). The role of chronic administration of antiplatelet drugs in primary prevention of arterial vascular events is known to be less clear than in secondary prevention, and, also in diabetic patients, the decision to give primary prophylaxis should be taken on an individual-patient basis, after a careful evaluation of the balance between the expected benefits and the risk of major bleedings. Although, currently, treatment has proven useful in reducing vascular events, diabetic patients continue to have a higher risk of adverse cardiovascular events compared with those in nondiabetic patients. This paper reviews the role of currently available antiplatelet drugs in primary and secondary prevention of vascular events in diabetic patients and the limitations of these drugs, and it discusses the role of novel and more potent antiplatelets and of new agents currently under clinical development.